Analisis Dampak Pembelajaran Daring Pada WLB (Work Life Balance) Mahasiswa Pekerja (Studi Kasus Mahasiswa Manajemen) - Mutiara Cantika Putri; Enjang Suherman; Dwi Epty Hidayati (Jurnal Mirai Management, 2025)
Students who study while working need to have a work-life balance. This is to ensure a smooth balance between their study and work lives. This study explains how online learning impacts the work-life balance of students who study while working and whether students are able to achieve work-life balance when faced with concurrent coursework and work assignments. This research method uses a qualitative research method with a phenomenological approach. Participants were selected using a purposive sampling method on a homogeneous sample. The participants were three students. Data collection techniques included observation and in-depth interviews. Data analysis used coding, categorization, and themes. The results of this study explain the existence of work-life balance strategies among students who study while working, the various reasons why students want to study while working, and the difficulties experienced by students while working. Thus, each individual has a work-life balance strategy when carrying out study while working.